Sources of risk and related effects in the Malaysian construction industry - Wong, Timothy Leong Urn (Universiti Malaysia Sarawak, UNIMAS, 2010)
The construction industry nowadays has higher complexities with increased scope of work, number of players involved and is technically more advanced. However, the industry does not give adequate attention to proper risk management. Key risks need to be identified and assessed and methods on risk mitigation need to be mapped out to cater for these risks. Even the smallest mistake or unforeseen risk can lead to major lost and even bankruptcy to construction firms. Therefore, the aim of this paper is to provide a compilation of risk and effects of risk data for the Malaysian construction industry. The overall discussion will focus on the sources of risk related to each specific group; the direct effects of these risks, and also the correlation between the sources and effects. The data is collected by conducting structured questionnaire surveys and distributing it out to government agencies, quantity surveyors, consultants and contractors involved in the construction industry. An in depth study is also done on different methods of risk identification available in project management. Results of risk identification from other countries have been studied and compared to make this paper more comprehensive. It is hoped that through this research, a proper knowledge or risk retention centre can ultimately be created using the data compiled here and also from future research. Data can also be extracted from this centre to aid accurate qualitative and quantitative risk analysis. This is crucial for future risk assessments and management for the construction industry.